Status of the Connection between Unidentified Egret Sources and Supernova Remnants: The Case of Cta 1 - Torres, Diego F. (2004)
In this paper we briefly comment on the observational status of the possible physical association between unidentified EGRET sources and supernova remnants (SNRs) in our Galaxy. We draw upon recent results presented in the review by Torres et al. (2003), concerning molecular gas in the vicinity of all 19 SNRs found to be positionally coincident with EGRET sources at low Galactic latitudes. In addition, we present new results regarding the supernova remnant CTA 1. Our findings disfavor the possibility of a physical connection with the nearby (in projection) EGRET source. There remains possible, however, that the compact object produced in the supernova explosion be related with the observed γ-ray flux.